REMOTE MEASUREMENT OF THE ATMOSPHERE LOWER LAYERS TEMPERATURE PROFILE BY MEANS OF RADIO POLARIMETRY - E. A. Bolelov; A. I. Kozlov; V. J. Maslov (Научный вестник МГТУ ГА)
Air temperature is one of the most important parameter of the atmosphere. The air temperature, especially in the lower atmosphere can have a significant effect on the aerodynamic characteristics of aircraft and is one of the main elements for the preparation of aviation weather forecasts. Methods of air temperature measuring in the atmosphere can be divided into two groups. The first group which combines the methods of contact measurement assumes the direct contact of the meter with the environment. The second group of methods, is now rapidly developing, combines the methods of remote measurement of the temperature. The problem of remote measurement of air temperature in the lower atmosphere is an important task, since the contact measurements, though highly accurate and informative, are held through certain and large enough time intervals (up to two times per day). To solve the problem of remote measurement of air temperature many different theoretical solutions and technical devices developed on their basis are proposed.  All the proposed methods and techniques have limitations on their use imposed primarily by the precision with which you can define certain characteristics of the studied objects. The article considers a method that opens up the possibility of solving the problem of remote measurement of temperature in non-uniformly heated environment without losses of atmosphere type. It is based on radio emission own reception, intensity of which depends on its temperature. The proposed method of air temperature remote measurement is based on the well-known formula of S. T. Egorov and Y. M. Shestopalov. The article gives reasons for the possibility of using elliptical antennas for air temperature remote measurement in the lower layers of atmosphere.